Knowledge of the Cigarettes Dangers and Attitudes about Cigarettes on the Intention to Quit Smoking in Teenagers Smokers in Nganjuk District - Reni Nurhidayah; Katmini; Prima Dewi Kusumawati; Ratna Wardani (Universitas STRADA Indonesia, 2023)
Background: The 2019 Global Youth Survey shows data that 19.2% or 50 million young man and women 13-15 years old smoke worldwide. BPS data through the 2021 Susenas shows that teenage smokers in Nganjuk Regency are 20.12%. The high prevalence of teenage smokers indicates the need for intervention to reduce the number of adolescent smokers as quickly as possible. Purpose: This study aims to determine the relationship between knowledge of the dangers of smoking and attitudes toward smoking with the desire to stop smoking in adolescents in the Nganjuk Regency. Methods: An observational design with a cross-sectional approach was used in this study. The sample in this study was 300 respondents who were taken using cluster sampling from 10 junior high schools in Nganjuk Regency. There are three questionnaires that use in this study. Data analysis used the Pearson correlation test and Linear Regression. Results: The percentage of teenage smokers in Nganjuk Regency is quite high at 33% with a dominance of male youth who start smoking by 11% at the junior high school level. P-value of 0.00 (> 0.05), which means that there is a relationship between attitudes about cigarettes and knowledge of cigarette dangers on intention to quit smoking. Beta value (0.311 > 0.193) said that attitudes about cigarettes have a 31.1% effect in making someone have the intention to quit smoking in a negative relationship. Conclusion: Attitudes about cigarettes variable have a stronger influence on intention to quit smoking than knowledge of cigarette. This shows that to increase the success of the smoking cessation program for adolescents in Nganjuk District, interventions are needed to increase negative attitudes and knowledge of the dangers of smoking.